Culture, gender and small business : Honiara, Solomon Islands : presented in partial fulfilment of the requirements of the degree of Master of Philosophy in Development Studies at Massey University - Simiha, Bella (Massey University, 2001)
The common assumption in regards to indigenous Solomon Islanders owning business is that most of these businesses will fail because of cultural constraints. These appear in the form of the wantok system and cultural obligations that place an extreme financial burden on small business owners (SBOs) and restrict the potential of potential small businesses. This study has been carried out in the formal business sector in Honiara to ascertain the effects of cultural obligations on small business (SB) and to determine the role of women in business. The research findings lead to the conclusion that with education/ experience cultural obligations can be managed within small businesses, and that women, despite the gender restrictions rooted in traditional culture, can manage small businesses successfully. However, it is evident that the wantok system and the commercialisation of some aspects of culture, places a financial burden on Solomon Islanders. In order to promote the development of indigenous small businesses, the government, pending adequate research, will need to ensure that suitable financial loan assistance schemes, and advisory offices are introduced to allow for easy access to start up business resources. Furthermore, as the research has shown that if women are to be successful in business these schemes must target all groups of women and not favour one group, for example rural women. It is also evident from the research that more professional women are entering into small businesses, and that they can manage cultural obligations and still assist relatives both in the urban and rural sectors.
Keywords: Solomon Islands -- Honiara; Women-owned business enterprises; Case studies; Small business; Businesswomen -- Developing countries; Oceania